Fluoride varnishes with calcium glycerophosphate: fluoride release and effect on in vitro enamel demineralization - Thiago Saads CARVALHO; Bianca Glerean PETERS; Daniela RIOS; Ana Carolina MAGALHÃES; Fabio Correia SAMPAIO; Marília Afonso Rabelo BUZALAF; Marcelo José Strazzeri BÖNECKER (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aims of this study were (1) to assess the amount of fluoride (F) released from varnishes containing calcium glycerophosphate (CaGP) and (2) to assess the effect of the experimental varnishes on in vitro demineralization. Six test groups using 5 varnishes: base varnish (no active ingredients); Duraphat® (2.26% NaF); Duofluorid® (5.63% NaF/CaF2); experimental varnish 1 (1% CaGP/5.63% NaF/CaF2); experimental varnish 2 (5% CaGP/5.63% NaF/CaF2); and no varnish were set up. In stage 1, 60 acrylic blocks were randomly distributed into 6 groups (n = 10). Then 300 µg of each varnish was applied to each block. The blocks were immersed in deionized water, which was changed after 1, 8, 12, 24, 48 and 72 hours. Fluoride concentration in the water was analyzed using a fluoride electrode. In stage 2, 60 bovine enamel samples were distributed into 6 groups (n = 10), and treated with 300 µg of the respective varnish. After 6 h the varnish was removed and the samples were subjected to a 7-day in vitro pH cycle (6 h demineralization/18 h remineralization per day). The demineralization was measured using surface hardness. The results showed that both experimental varnishes released more fluoride than Duofluorid® and Duraphat® (p < 0.05), but Duraphat® showed the best preventive effect by decreasing enamel hardness loss (p < 0.05). Therefore, we conclude that even though (1) the experimental varnishes containing CaGP released greater amounts of F, (2) they did not increase in the preventive effect against enamel demineralization.